Leading creative teams : management career paths for designers, developers, and copywriters - Hernández, Eleazar (Apress, 2017)
Learn the skills you must master to assume leadership roles--creative directors, art directors, and advertising managers--on creative teams and in integrated branding campaigns for corporate clients. This book compares and contrasts the skill sets and responsibilities of creatives with those of managers who direct creative teams. Technical competence in the creative arts is a necessary but not sufficient prerequisite for promotion to and success in positions directing creative teams. Business, management, and communication skills are equally necessary. Leading Creative Teams reviews the business metrics that the manager of a creative team must be able to manipulate and present persuasively to the organization to prove that the team's creative excellence delivers superior ROI. Award-winning designer and veteran creative director Eleazar Hernández walks you through the creative manager's skill sets--technical, business, management, and communication. He covers the techniques and tools common to the direction of creative teams in all industries: brainstorming, creative exploration and visual communication tools, internal and client presentations, critiquing, mentoring, and copywriting.
Keywords: Teams in the workplace.; elektronické knihy; electronic books